Catanduba, a new Theraphosinae spider genus from Central Brazil (Araneae, Theraphosidae) - Yamamoto, Flávio U.; Lucas, Sylvia M.; Brescovit, Antonio D. (Zootaxa, 2012)
A new genus, Catanduba, is proposed and supported on the cladistic analysis with the following synapomorphies: em-bolus tapering abruptly from half of the length, embolus tooth associated with PIK and a triangular basal nodule on malemetatarsus I. Homoeomma simoni and Plesiopelma flavohirtum are transferred to Catanduba and five new species are de-scribed: C. tuskae, C. araguaia, C. piauiensis, C. canabrava and C. peruacu. The species occur mainly in central Brazil,in Cerrado areas, with some species also occurring in Atlantic forest (C. tuskae sp. n. ) and Caatinga (C. piauiensis sp. n. and C. peruacu sp. n.).